Controle genético da coloração do tegumento e da concentração de ferro em sementes de feijão mesoamericano e andino - Possobom, Micheli Thaise Della Flora (2014)
The acceptance of the beans by consumers is related to seed coat color and nutritional value. The objectives of this work were: (1) to verify the existence of maternal effect for the color parameters "L", a* and b* and for the iron concentration in Middle American and Andean common bean seeds; (2) to investigate the distribution of iron in the seed coat and embryo of the Middle American and Andean common bean seeds; (3) to estimate heritability and gain with the selection for the parameters "L", a* and b* and for the iron concentration in common bean seeds of different gene pools; and (4) to select recombinant with seed coat color of highest commercial demand and with high iron concentration in the seeds. To do this, were performed controlled crosses between Middle American lines CNFP 10104 and CHC 01-175, and Andean lines Cal 96 and Hooter to obtain F1, F1 reciprocal, F2, F2 reciprocal and backcrosses (RC11 e RC12) generations for each hybrid combination. Parents and generations obtained were evaluated in two field experiments (normal rainy and dry season) in Santa Maria - RS. Significant maternal effect was obtained for all color parameters in the Middle American and Andean gene pool. In CNFP 10104 x CHC 01-175 crossing high broad sense heritability estimates were obtained for luminosity (h2b: 76.66 to 78.09%), chromaticity a* (h2b: 73.08 to 89.31%) and chromaticity b* (h2b: 88.63 to 90.11%) values in normal rainy and dry season. In Cal 96 x Hooter crossing the parameters luminosity (h2b: 95.07%), chromaticity a* (h2b: 86.19%) and chromaticity b* (h2b: 92.50%) showed high broad sense in dry season. For iron concentration, maternal effect was significant only for the Middle American gene pool. The iron concentration was higher in seed coat of Middle American lines, and superior in embryo of Andean lines. Estimates of narrow sense heritability for the iron concentration of 54.69% and broad sense heritability of 70.20% for CNFP 10104 x CHC 01-175 crossing and broad sense heritability of 62.27% for Cal 96 x Hooter crossing were observed. A F2 plant with iron concentration of 132.99 mg kg- 1 of dry matter was obtained from CNFP 10104 x CHC 01-175 crossing. The selection of F3 seeds (seed coat in F2) from the crossings performed should be promising to obtain common bean lines with seeds colored according to the market demand and with high iron concentration in seeds.